METAPHORS ANALYSIS IN LYRICS OF COLDPLAY’S SONGS - Aziz Vikri, Muhammad; Achmad Nurcholis, Ivan (Pusat Riset dan Inovasi Nasional, 2022)
This paper is entitled “Metaphors Analysis In Lyrics Of Coldplay’s Songs” discusses about the types of metaphor found in this songs. In this paper, the writer used library research method by collected metaphor data then analysed and determined the most dominant. This study uses the theory of Parera who classified metaphor into anthropomorphic metaphor, animal metaphor, a metaphor from concrete to abstract, and synesthetic metaphor.In these three selected songs of coldplay’s song, the writer found 14 metaphor consist of 5 Anthropomorphic Metaphor, 2 Animal Metaphor, 2 A Metaphor From Concrete To Abstract, and 6 Synesthetic Metaphor. Synesthetic Metaphor turns out to be the most dominant while Animal Metaphor and A Metaphor From Concrete To Abstract is the least.